Building Systems Testing Method Using Ishihara Color Blindness - Faduhusi Lombu; Erwin Panggabean (Journal of Computer Networks, Architecture and High Performance Computing, 2020)
Color blind test system is needed in various needs such as the management of a driver's license, prospective students in Certain institutions, prospective employees or employees in government and private agencies. The development of a computer-based test system color blind color blind tests aims at activities that produce normal eye Conclusions on sealing, partial color blindness and total color blindness. The method used to complete this research is Ishihara, which was discovered by Dr. Shinobu Ishihara. For the construction of the Ishihara color-blind method of testing using the stages of analysis, design and implementation. The developed test system aims to be used as a color blind tests for the health test requirements as a requirement for prospective employees at PT JAVA GLOBAL FUTURES Medan. To build this color blind test system used MS-Visual Studio 2010 and the results were made using Crystal Report 2010. This research has produced a Color Blind Test System with the Ishihara roomates Computer Based Method is used for the color blind tests at PT JAVA GLOBAL FUTURES Medan. With the output in the form of computer screens and paper prints when using a printer connected to a computer in the form of a Health Certificate with test results in the form of a normal eye vision, color blindness partial or total color blindness.